(untitled) (International Journal of Physiotherapy, 2017)
Introduction: Neuromodulation in its various forms is emerging as a promising method of dealing with chronic pain and movement disorders. The scale of ablative vs augmentative procedures seems to be tilting towards augmentative procedures. We observed 8 patients who had failed medical treatment for muscle spasm respond to the cold application. Case summary: We report 2 cases of complete traumatic spinal cord injury patients, who developed severe, medically intractable muscle spasms. We applied cryotherapy to their legs with significant improvement. Outcome measurements: The spasm frequency score dropped immediately from a 4 to 0 in one patient. The other dropped from a 2 to 1 on day one then disappeared by day 7. Spasm severity dropped significantly on the first day in both cases. Conclusion: Cryotherapy as a form of neuromodulation, Is an effective, simple but safe way to symptomatically manage severe medically refractory muscle spasms in spinal cord injured patients. It becomes an important adjunct in the management of these patients in resource-limited settings where surgical options are not readily available.